2016
DOI: 10.1177/107327481602300315
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Stereotactic Radiotherapy for Auditory Canal or Middle Ear Cancer

Abstract: These results suggest that SRT outcomes are promising for patients with ear cancer (? T3 disease). The rate of toxicity was acceptable in the study patients treated without boluses. Outcomes of salvage surgery and postoperative radiotherapy following SRT were also encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Especially, cure rates of the early lesions (T1 and T2) treated by en-bloc resection were near to 100%. 6) Relatively favorable oncological results have been reported on radiotherapy alone for T1 and T2 by Murai et al 11) . They reported that local control rate of T1 and T2 patients is 70%.…”
Section: Discussionmentioning
confidence: 97%
“…Especially, cure rates of the early lesions (T1 and T2) treated by en-bloc resection were near to 100%. 6) Relatively favorable oncological results have been reported on radiotherapy alone for T1 and T2 by Murai et al 11) . They reported that local control rate of T1 and T2 patients is 70%.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that the modified Pittsburgh classification distinguishes in overall survival (OS) between the four T-classifications. 8,11,13,[15][16][17][18][19] As (local) recurrent or residual disease can have a serious impact on the patients quality of life, DFS should be considered a more clinically relevant outcome measurement for EAC SCC. However, the predictive potential of the Pittsburgh classification to predict the DFS of individual patients with EAC SCC has not yet been evaluated in a large study sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, the AJCC classification is mainly based on the diameter of the tumor and the modified Pittsburgh classification on the erosion of anatomical structures by the tumor. Several studies have shown that the modified Pittsburgh classification distinguishes in overall survival (OS) between the four T‐classifications 8,11,13,15‐19 . As (local) recurrent or residual disease can have a serious impact on the patients quality of life, DFS should be considered a more clinically relevant outcome measurement for EAC SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Radical conventional radiotherapy also achieves favorable outcome, which was considered as treatment option (14). Murai et al reported the effectiveness of the stereotactic radiotherapy for a new treatment option of EACC (15).…”
Section: Discussionmentioning
confidence: 99%